Narrow‐wide‐row planting pattern increases the radiation use efficiency and seed yield of intercrop species in relay‐intercropping system. (18th May 2019) - Raza, Muhammad Ali; Feng, Ling Yang; van der Werf, Wopke; Cai, Gao Ren; Khalid, Muhammad Hayder Bin; Iqbal, Nasir; Hassan, Muhammad Jawad; Meraj, Tehseen Ahmad; Naeem, Muhammd; Khan, Imran; Rehman, Sana ur; Ansar, Muhammad; et al.
Abstract: Planting arrangements affect radiation use efficiency (RUE) and competitiveness of intercrop species in intercropping systems. Here, we reveal that narrow‐wide‐row planting arrangement in maize‐soybean relay‐intercropping system increases the dry matter and competitiveness of soybean, increased the RUE of maize and soybean, and compensates the yield loss of maize by substantially increasing the yield of soybean. In this field study, maize was planted with soybean in different planting arrangements (P1, 20:180, P2, 40:160; P3, 60:140, and P4, 80:120) of relay intercropping, all the relay‐intercropping treatments were compared with sole crops of maize (SM) and soybean (SS). Results showed that P1 improved the total RUE 3.26 g/MJ (maize RUE + soybean RUE) of maize and soybean in relay‐intercropping system. Compared to P4, treatment P1 increased the soybean competition ratio (CR) values (by 55%) but reduced the maize CR values (by 29%), which in turn significantly improved the yield of soybean by maintaining the maize yield. Generally, in P1, soybean produced 82% of SS yield, and maize produced 88% of SM yield, and it achieved the land equivalent ratio of 1.7. These results suggest that by maintaining the appropriate planting distances between maize and soybean we can improve the competitiveness and yield of intercrop species in relay‐intercropping system. Abstract : Here, we reveal that narrow‐wide‐row planting arrangement in relay‐intercropping system increased the dry matter production and competitiveness of soybean plants, enhanced the RUE of intercrop‐species, and compensates the slight maize yield loss by considerably increasing the soybean yield.